COVID‐19 and home confinement: A study on fathers, father–child relationships and child adjustment. (22nd September 2021) - Trumello, Carmen; Bramanti, Sonia M.; Lombardi, Lucia; Ricciardi, Piera; Morelli, Mara; Candelori, Carla; Crudele, Monia; Cattelino, Elena; Baiocco, Roberto; Chirumbolo, Antonio; Babore, Alessandra
Abstract: Background: The purpose of this study was to explore fathers' adjustment and father–child relationships during the first peak of the coronavirus disease 2019 (COVID‐19) outbreak (April 2020). More particularly, the study analysed paternal perceptions of changes concerning familial economic conditions and children's psychological difficulties (viz., emotional problems and hyperactivity) during the lockdown produced by the current pandemic. Furthermore, we investigated the following correlates of fathers' parenting stress: socio‐demographic condition, paternal individual stress, anxiety, depression and changes in the father–child relationship during the outbreak. Methods: A total of 102 fathers (mean age = 41.60 years; SD = 11.54) with minor children were recruited through an online survey and reported data about their socio‐economic condition, anxiety, and depressive levels, parenting stress, offspring's adjustment, and changes in their relationship with their children. Results: As for the economic conditions, participants were equally distributed between those who did not perceive changes and those who perceived a worsening. With regard to changes in the child's psychological difficulties, results showed that levels of children's emotional problems and inattention/hyperactivity had significantly increased during the lockdown period. A multiple linear regression analysis highlighted that the principal predictor of paternal parenting stress was living in the regions most affected by the COVID‐19 pandemic, followed by high levels of paternal anxiety symptomatology and high levels of worsening of the relationship with the child during the pandemic. Conclusions: Overall, our study suggests to consider the effects of COVID‐19 on fathers as well, as they have been rather overlooked by previous research that has mainly focused on mothers, and to plan specific interventions able to also take them into account.